TOWARDS A FRAMEWORK FOR PROFESSIONAL DEVELOPMENT: THE IMPLICATIONS OF INDIVIDUAL PLANS IN TEACHER ADVANCEMENT - Malabanan, Amber (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This study develops a framework for professional development, focusing on the implications of individual plans for teacher advancement. As education systems increasingly emphasize personalized professional growth, individual development plans (IDPs) are recognized as a key strategy for enhancing teachers’ skills, knowledge, and overall performance. Through a mixed-methods approach, including surveys of teachers, interviews with educational leaders, and case studies of schools that implement IDPs, the research explores how individualized professional development plans contribute to teachers’ career progression, motivation, and job satisfaction. Findings indicate that IDPs enable teachers to take ownership of their development, align their goals with school objectives, and engage in targeted, reflective learning experiences. The study also identifies the challenges and best practices for designing and implementing effective IDPs, emphasizing the role of school leadership in supporting teachers through mentoring, feedback, and resources. The proposed framework offers a holistic approach for schools to foster continuous teacher advancement and improve overall teaching quality.